CHARACTERISTIC TESTING OF THE GROUND CABLE USING TAN DELTA (TD) TEST METHOD ON TWO SEGMENTS OF THE MEDIUM VOLTAGE CABLE MENTENG AREA - Christiono Christiono; Miftahul Fikri; Iwa Garniwa; Dani Maula Sattar; Andi Amar Thahara (Department of Computer Engineering, Universitas Wiralodra, 2022)
This research is based on the existence of underground cable problems due to rainfall in certain areas, especially the Central Jakarta area results in an increase in soil moisture that can degrade the dielectric strength of the SKTM and potentially SKTM interference. Therefore, Tan Delta testing method is carried out as a predictive step to analyze the cable health condition and an early method to determine the good/bad of the test cable. After testing tan delta, it was obtained that the acquisition of segment 1 data results were in good condition because the average value of delta tan in all three phases was 1.0, with the differential results being 0.0 and deviation standard 0.0. Action to segment 1 is periodic maintenance of 5 years. Then in segment 2, the data obtained the average value of tan delta phase R 70.6, phase S 143.9, and phase T 83.92. For differential of phase R 161.7, phase S 33.7, and phase T 135.08. Finally, deviation standard at phase R 4.57, phase S 20.14, and phase T 2.43. From IEEE 400.2-2013 standard, it can be concluded that segment 2 is in poor condition and need action as soon as possible of PD Tests and cable replacement